Non-emergency attenders at a district general hospital accident and emergency department. Issue 4 (December 1995) - Thomson, H; Kohli, H S; Brookes, M
Abstract : Following concern about long waiting times, a survey was carried out in the Accident and Emergency (A&E) department of Monklands District General Hospital over 5 consecutive days to investigate factors related to the bypassing of general practitioners (GPs) by 'self-referred' patients and inappropriate use of the department. Two hundred and forty-five (90.7%) of 270 non-emergency patients who attended the department during GP surgery hours completed a self-administered questionnaire. Variables measured included recent use of health services, perceptions of the GP service and the A&E service and reasons for bypassing the GP. Of the 245 patients, 49 (20%) were defined as inappropriate and 152 (62%) were self-referred. Self-referred patients were no more likely to use the A&E department inappropriately than those who were referred.